RECOGNITION AND DEALING WITH ATHLETES' ANXIETY - Radovan Čokorilo (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The work analizes the impact of excitement, anxiety and stress on athletes. The most common causes of anxiety have been reviewed (increased muscle tension, difficul- ties in movement coordination, differences in attention and concentration levels) and so have the co-factors on the road from excitement to performance: character, the comple- xity of the task, and the presence of an audience. The most important strategies of recog- nition of, and dealing with, anxiety are thus proposed: identification the optimum combi- nation of emotions, recongition of personal and situation-caused factors, recognition of athletes' anxiety symptoms, individual training strategy and developing self confidence